Convergência na educação: políticas, tecnologias digitais e relações pedagógicas - Fernanda Araujo Coutinho Campos (2017)
In these times of the so-called information society, we have been aware of social, cultural, political, economic and, of course, educational changes. Among the various changes in the educational field, we have focused on the changes derived from the existence and development of the information and communications digital technologies that promoted reflections on traditional educational paradigms, ways of teaching and learning, time and space, expansion of knowledge exchange spaces, educational policies, face-to-face and distance modalities; as well as in ways of relating and producing new knowledge that involves collaboration, sharing, participation, horizontality, learning communities, interaction, mediation, virtual learning environments, socialization, autonomy and networking. In this tangle of situations and provocations, we hypothesized that the convergence observed in other areas of knowledge - technology, communication and arts - and the increasingly constant use of distance learning, combined with face-to-face teaching, would be the basis of convergence in education. Thus, this work has the goal of understanding convergence in education as a possibility to higher education; and as specific goals, to question current education policies in the context of higher education, relating the offerring of distance learning subjects in face-to-face teaching; conceptually characterize the convergence in education; identify elements of convergence in education; to review on the notions of presence and distance. To do so, the methodology employed on this research was divided into two axes: (1) analytical, in which public policies, the meanings of convergence, the elements of convergence and the presence and the distance stand out; and (2) operational, in which the research was developed through the philosophical methodology, the documental analysis and the Internship (conducted between August 2014 and September 2015 at Universidade Aberta de Portugal-UAb). As final considerations, we verified that convergence, above all, is social. It is done among the relationships created by networking and mediated by TDIC (Information and Communications Digital Technology) as well as broaden educational paradigms, places of teaching and learning, relationships between subjects - teachers and students. In addition, convergence is seen as a tendency of the present with eyes towards the future.